Value of proprotein convertase subtilisin/kexin type 9 and inflammatory markers in the diagnosis of carotid atherosclerosis in hypertensive men - Yu. Yu. Vukolova; E. Yu. Gubareva; I. V. Gubareva; O. A. Germanova; G. I. Kiseleva (Российский кардиологический журнал, 2024)
Proprotein convertase subtilisin/kexin type 9 (PCSK9) is involved in lipid metabolism, has local and systemic effects in immunoregulation and atherogenesis in hypertensive patients.Aim. To personalize cardiovascular risk (CVR) stratification taking into account the diagnostic value of PCSK9 and inflammatory markers in men with hypertension and carotid atherosclerosis.Material and methods. The study included 162 males with stage I-III hypertension of various CVR. All patients underwent collection of complaints and medical history, physical examination with anthropometry. The following laboratory test were performed: complete blood count with white blood cell differential and erythrocyte sedimentation rate, assessment of fibrinogen, C-reactive protein (CRP), total cholesterol, low-density lipoprotein cholesterol, triglycerides, blood glucose, serum creatinine level. Glomerular filtration rate and microalbuminuria were also evaluated. Serum PCSK9, interleukins-8, 10 (IL-8, 10) were determined by enzyme immunoassay. In addition, 24-hour blood pressure monitoring, extracranial artery ultrasound with determination of intima-media thickness and carotid stenosis severity were performed. Patients were divided into 3 groups according to PCSK9 level.Results. Analysis of conventional cardiovascular factors and cytokine status (IL-8 and IL-10) in patients showed an inverse relationship between age and IL-8 (r=-0,230; p=0,036), IL-8/IL-10 (r=-0,309; p=0,005); heredity and IL-8/IL-10 (r=-0,423; p=0,001). There were following relationships between CVR factors and PCSK9: direct relationship between men's age (r=0,220, p=0,032), systolic and diastolic blood pressure (r=0,230, p=0,033; r=0,260, p=0,015) and PCSK9; inverse relationship between PCSK9 and heredity (r=-0,286, p=0,011). C-reactive protein and erythrocyte sedimentation rate were associated with IL-10 levels, which are associated with anti-inflammatory activity (r=0,78; p=0,02; r=0,78; p=0,02, respectively). The IL-8/IL-10 cytokine imbalance was most pronounced in patients with a night-peaker 24-hour systolic blood pressure profile (p=0,02). Patients with intima-media thickening and plaques had a highest level of PCSK9 (p=0,006). IL-8 levels were significantly higher with unchanged intima-media thickness (p=0,01).Conclusion. In patients with high levels of PCSK9, there is a close relationship between risk factors for hypertension and cytokine imbalance. The severity of extracranial artery atherosclerosis significantly depends on the increase in the levels of PCSK9 (p=0,006) and inflammatory markers (IL-10) (p=0,044).